Chemical composition comparison of n-hexane extract and essential oil kemenyan toba (Styrax sumatrana) sap from Tobasa North Sumatera by GC-MS and in silico study its compound as antiinflammatory - Kamilia Mustikasari; Mardi Santoso; Nadia Sasanti; Maria Dewi Astuti; Taslim Ersam; Noer Komari (Jurnal Riset Industri Hasil Hutan, 2022)
The sap of kemenyan toba (Styrax sumatrana) is often used as a binder for perfumes, raw materials for cosmetics and medicines, so it is widely traded. However, not many studies have reported about its chemical composition. The process of extracting chemical compounds from kemenyan toba (S. sumatrana) sap quality one was carried out by maceration method using n-hexane and water distillation. The result of maceration was 25.3% of the n-Hexane extract, while the distillation yielded 0.13% (w/w) of a pale-yellow oil. The results of the GC-MS analysis showed that only benzoic acid was present in the extracts and essential oils. n-Hexane extract consists of styrene compounds, cinnamic acid, benzyl benzoate, 1,4-diphenyl-1.4-butanedione, benzyl cinnamates, methyl styrene, and cinnamyl cinnamate. In comparison, essential oil consists of 3-methylpentan-2-one, methyl palmitate, methyl stearate, methyl trans-9.10-epoxystearate, dioctyl hexanedioic, methyl oleic, and methyl-13.16-Octadecanoic. The in-silico test results of several compounds as antiinflammatory showed that the compounds cinnamyl cinnamate had potential as an anti-inflammatory.